Complementing the Latest APA Definition of Hypnosis: Sensory-Motor and Vascular Peculiarities Involved in Hypnotizability. Issue 3 (2nd July 2016) - Santarcangelo, Enrica L.; Scattina, Eliana
Abstract: The aim of this article is to complement the recently revised American Psychological Association (APA) definition of hypnotizability. It (a) lists a few differences in sensorimotor integration between subjects with high (highs) and low (lows) hypnotizability scores in the ordinary state of consciousness and in the absence of suggestions, (b) proposes that hypnotizability-related cerebellar peculiarities may account for them, (c) suggests that the cerebellum could also be involved in cognitive aspects of hypnotizability and (d) explains why the information derived from studies of sensorimotor and cardiovascular aspects of hypnotizability may be relevant to its definition and useful in orienting further experimental research in the field of hypnosis.